Stylistics and Narrative Linguistics in Digital Journalism: An Analysis of Metro TV's Meet Nite Live Program - Souisa, Dea; Nensilianti; Mahmudah (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
This study aims to analyze the use of stylistic devices and narrative structures in the Meet Nite Live program on Metro TV’s YouTube channel as a representation of digital journalism practices. This study employs a descriptive qualitative approach using content analysis. The data consists of transcribed verbal utterances from the episode “Kuota Haji Kini Jadi Ladang Investasi Rawan Korupsi”. The analysis was conducted using Geoffrey Leech’s stylistic framework to identify linguistic strategies, as well as Labov and Waletzky’s narrative theory to examine narrative structure. The results indicate that the language style in this program is dominated by three primary strategies: figures of speech, foregrounding, and lexical choice, which serve to build appeal while reinforcing the credibility of the journalistic narrative. The use of satire, hyperbole, parallelism, and hybrid diction has proven effective in creating an emotional connection with the digital audience without compromising the substance of the information. Meanwhile, the narrative structure is dynamically organized through six main elements (abstract, orientation, complication, evaluation, resolution, and coda) with a non-linear pattern, such as the repetition of orientation and the distribution of evaluation across various points in the narrative. This pattern indicates that digital journalistic narratives not only convey facts but also gradually construct social meaning. These findings confirm that the integration of stylistic elements and narrative structure is a key strategy for creating engaging, contextual, and credible journalistic discourse in the digital media era.